Gb3‐cSrc complex in glycosphingolipid‐enriched microdomains contributes to the expression of p53 mutant protein and cancer drug resistance via β‐catenin–activated RNA methylation - Kartik R. Roy; Mohammad B. Uddin; Sagor C. Roy; Ronald A. Hill; John Marshall; Yu‐Teh Li; Jean Christopher Chamcheu; Hua Lu; Yong‐Yu Liu (FASEB BioAdvances, 2020)
Abstract Glucosylceramide synthase (GCS) is a key enzyme catalyzing ceramide glycosylation to generate glucosylceramide (GlcCer), which in turn serves as the precursor for cells to produce glycosphingolipids (GSLs). In cell membranes, GSLs serve as essential components of GSL‐enriched microdomains (GEMs) and mediate membrane functions and cell behaviors. Previous studies showed that ceramide glycosylation correlates with upregulated expression of p53 hotspot mutant R273H and cancer drug resistance. Yet, the underlying mechanisms remain elusive. We report herewith that globotriaosylceramide (Gb3) is associated with cSrc kinase in GEMs and plays a crucial role in modulating expression of p53 R273H mutant and drug resistance. Colon cancer cell lines, either WiDr homozygous for missense‐mutated TP53 (R273H+/+) or SW48/TP53‐Dox bearing heterozygous TP53 mutant (R273H/+), display drug resistance with increased ceramide glycosylation. Inhibition of GCS with Genz‐161 (GENZ 667161) resensitized cells to apoptosis in these p53 mutant‐carrying cancer cells. Genz‐161 effectively inhibited GCS activity, and substantially suppressed the elevated Gb3 levels seen in GEMs of p53‐mutant cells exposed to doxorubicin. Complex formation between Gb3 and cSrc in GEMs to activate β‐catenin was detected in both cultured cells and xenograft tumors. Suppression of ceramide glycosylation significantly decreased Gb3‐cSrc in GEMs, β‐catenin, and methyltransferase‐like 3 for m6A RNA methylation, thus altering pre‐mRNA splicing, resulting in upregulated expression of wild‐type p53 protein, but not mutants, in cells carrying p53 R273H. Altogether, increased Gb3‐cSrc complex in GEMs of membranes in response to anticancer drug induced cell stress promotes expression of p53 mutant proteins and accordant cancer drug resistance.